2018
DOI: 10.1111/lam.13017
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of spray-drying conditions and postdrying storage time and temperature on Salmonella choleraesuis and Salmonella typhimurium survival when inoculated in liquid porcine plasma

Abstract: Safety of raw materials from animal origin like spray-dried porcine plasma (SDPP) may be a concern for the swine industry. Spray-drying process and postdrying storage are good inactivation steps to reduce the bacterial load of Salmonella choleraesuis and Salmonella typhimurium. For both Salmonella spp., spray-drying at 71°C or 80°C outlet temperatures reduced bacterial counts about 3 log at residence time (RT) 0 s, while there was about a 5.5 log reduction at RT 60 s. Storage of all dried samples at either 4.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Several viruses of concern to the swine industry, including the Porcine respiratory and reproductive syndrome virus (PRRSV), Pseudorabies virus (PRV), and Porcine epidemic diarrhea virus (PEDV), have been shown to be effectively inactivated by spray-drying [9][10][11][12], as well as bacteria such as Escherichia coli or Salmonella enterica [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several viruses of concern to the swine industry, including the Porcine respiratory and reproductive syndrome virus (PRRSV), Pseudorabies virus (PRV), and Porcine epidemic diarrhea virus (PEDV), have been shown to be effectively inactivated by spray-drying [9][10][11][12], as well as bacteria such as Escherichia coli or Salmonella enterica [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Liquid plasma is then concentrated and spray-dried at 80˚C throughout its substance to produce SDPP [3,4]. Spray-drying involves very rapid desiccation of the liquid [5], results in a dried powder with low moisture (< 9%) and very low water activity (aw < 0.6), which has a detrimental effect on bacteria and virus survivability, as has been shown for multiple bacteria and viruses of interest in swine industry [6][7][8][9][10][11][12]. Furthermore, some microorganisms, especially bacteria and enveloped viruses, are not able to survive for a prolonged time in dried materials like SDPP with very low water activity [3,5,8,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spray-drying as an intrinsic safety step in the manufacturing process of SDPP has been shown effective to inactivate different viruses of concern for the swine industry including porcine respiratory and reproductive syndrome virus (PRRSV), pseudorabies virus (PRV), swine vesicular disease virus and porcine epidemic diarrhea virus (PEDV) [ 18 , 27 29 ] as well as bacteria such as Escherichia coli or Salmonella enterica [ 30 , 31 ]. Pathogen inactivation by spray drying occurs due to the combination of rapid desiccation at high temperature [ 19 ], that results in damage to the cytoplasmic membrane [ 32 , 33 ], damage to genetic material and inactivation of other proteins including enzymes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many experiments of deliberated inoculation of pathogens in plasma have demonstrated that spray-drying is a very effective technology to inactivate important pathogens of interest in the swine industry. Pathogen inactivation results from studies using spray drying of plasma inoculated with Salmonella enterica [ 28 , 29 ] , E.coli enterotoxigenic strains [ 30 ], Porcine reproductive and respiratory syndrome virus (PRRSV) [ 31 ] , Pseudorabies virus (PRV) [ 31 ] , Swine vesicular disease virus (SVDV) [ 32 ], Porcine epidemic diarrhea virus (PEDV) [ 33 , 34 ] or African swine fever virus (ASFV) [ 35 ] are summarized in Table 1 . Furthermore, in Table 2 results from other studies are summarized demonstrating the lack of pathogen transmission in pigs provided feed with SDP containing virus genome.…”
Section: Industrial Production Of Spray-dried Plasma and Its Biosafetmentioning
confidence: 99%